The Implementation of School Rules on the Disciplinary Character of Students at SMA Negeri 1 Gunung Toar, Kuantan Singingi Regency - Maulani, Nadira; Arianto, Jumili; Supentri, Supentri (Journal of Educational Sciences, 2025)
This study was motivated by the lack of disciplinary character among students at SMA Negeri 1 Gunung Toar. The purpose of the research was to determine whether the implementation of school rules has an effect on the disciplinary character of students at SMA Negeri 1 Gunung Toar. This study employed a quantitative descriptive method. The population consisted of 380 students, with a sample of 95 students selected randomly. Data analysis was conducted using a simple linear regression test with the assistance of SPSS version 25. The results showed a positive and significant influence of school rules implementation on students’ disciplinary character, as evidenced by the calculated F value (62.430) being greater than the F table value (3.94). The coefficient of determination (R Square) was 0.402, indicating that the implementation of school rules accounts for 40.2% of the variance in students’ disciplinary character, while the remaining 59.8% (100% - 40.2%) is influenced by other variables not examined in this study.